Distinct expression and prognostic values of GATA transcription factor family in human ovarian cancer - Quan Zhou; Huai-jie Yang; Man-zhen Zuo; Ya-ling Tao (BMC, 2022)
Abstract Accumulated studies have provided controversial evidences of expression patterns and prognostic value of the GATA family in human ovarian cancer. In the present study, we accessed the distinct expression and prognostic roles of 7 individual members of GATA family in ovarian cancer (OC) patients through Oncomine analysis, CCLE analysis, Human Protein Atlas (HPA), Kaplan-Meier plotter (KM plotter) database, cBioPortal and Metascape. Our results indicated that GATA1, GATA3, GATA4 and TRPS1 mRNA and protein expression was significantly higher in OC than normal samples. High expression of GATA1, GATA2, and GATA4 were significantly correlated with better overall survival (OS), while increased GATA3 and GATA6 expression were associated with worse prognosis in OC patients. GATA1, GATA2, GATA3 and GATA6 were closely related to the different pathological histology, pathological grade, clinical stage and TP53 mutation status of OC. The genetic variation and interaction of the GATA family may be closely related to the pathogenesis and prognosis of OC, and the regulatory network composed of GATA family genes and their neighboring genes are mainly involved in Notch signaling pathway, Th1 and Th2 cell differentiation and Hippo signaling pathway. Transcriptional GATA1/2/3/4/6 could be prognostic markers and potential therapeutic target for OC patients.